Application of Sn0. 2Mo0. 8S2 nanoring and pressure and temperature sensing material of Sn0. 2Mo0. 8S2 nanoring

The preparation of Sn0.2Mo0.8S2 nanorings by wet chemistry and sprayed on the interfinger electrodes, solving the problems of complex preparation and poor flexibility of existing metal sulfide nanorings, and achieving flexible pressure and temperature transmission with high sensitivity and stability feel.

CN119306253APending Publication Date: 2025-01-14NINGXIA UNIVERSITY +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310890767.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-07-11
Filing Date
2023-07-20
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The existing preparation methods of metal sulfide nanorings are complex, and there are problems of impurities introduction and poor flexibility, making them difficult to apply in the fields of flexible pressure and temperature sensing.

Method used

The Sn0.2Mo0.8S2 nanorods were prepared by wet chemistry using SnS2 nanosheets, Sn0.3Mo0.7O3 nanorods and thiourea as precursors, and sprayed them on the interfinger electrode to form a flexible sensor to achieve pressure and temperature Monitor simultaneously.

Benefits of technology

It realizes flexible pressure and temperature sensing with high sensitivity and stability, can monitor motion signals, physiological signals and temperature signals, and has good tensile performance and charge transfer capabilities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119306253A_ABST
    Figure CN119306253A_ABST
Patent Text Reader

Abstract

The invention relates to application of a Sn0. 2Mo0. 8S2 nanoring and a pressure and temperature sensing material of the Sn0. 2Mo0. 8S2 nanoring, and belongs to the technical field of pressure sensors and temperature sensors. The invention discloses a Sn0. 2Mo0. 8S2 nanoring and application of the Sn0. 2Mo0. 8S2 nanoring as a flexible sensing material to a flexible pressure sensor which is easy to wear, comfortable, high in stability and high in sensitivity and a flexible temperature sensor which is high in sensitivity, and the sensing requirements of temperature and stress are met at the same time. Sn0. 2Mo0. 8S2 is sprayed on the surface of a flexible PET interdigital electrode and dried to form a film, the chemical resistance type flexible pressure / temperature sensor is prepared, temperature signal monitoring and monitoring of motion signals and physiological signals related to human health can be achieved, good repeatability and stability are achieved, and meanwhile the Sn0. 2Mo0. 8S2 pressure sensor further has the application potential of voice recognition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of pressure sensors and temperature sensors, and in particular to Sn 0.2 Mo 0.8 S 2 Preparation and testing of flexible pressure sensor and temperature sensor devices based on nanospheres. Technical Background

[0002] Pressure sensors can sense pressure signals and convert them into devices or apparatuses that can output electrical signals according to certain rules. By observing the changes in pressure signals, various signals related to physiological health, such as breathing and pulse changes, can be monitored. Temperature sensors are sensors that sense temperature changes and output them as readable signals. Generally, temperature sensors can be divided into contact and non-contact types according to the measurement method. In recent years, the main research direction and development trend of contact temperature sensors are semiconductor thermistors. They have the advantages of fast response and small size, and are used in production, military industry, medical treatment, etc.

[0003] Flexible pressure / temperature sensors are important components of many intelligent sensing systems. In recent years, two-dimensional (2D) materials have been widely studied in the field of sensors due to their unique advantages such as large specific surface area, ultra-thin sheet structure, and excellent physical and chemical properties. Metal sulfides are typical representatives of two-dimensional materials. Their unique physical and chemical properties make them widely used in optoelectronics, thermoelectrics, catalysis, sensing, ion exchange, energy storage and conversion. However, among the metal sulfides reported so far, nanosheet structures account for the vast majority, and sensors prepared based on metal sulfides have poor flexibility.

[0004] At present, metal sulfide two-dimensional materials of ultra-thin nanosheets are mainly used for flexible sensor devices. Metal sulfides with structures such as nanoframes and nanocircles have not yet been applied to the field of flexible sensing. At present, the main preparation method of nanocircle structure materials is a two-step synthesis method: first, the nanocircle material is grown using a template, and then the template is etched to obtain the nanocircle material. However, the preparation of metal sulfide nanocircles is still relatively difficult, with complex operations, more reaction conditions, and easy introduction of impurities during the etching process. Therefore, it is a reliable solution to etch the template by liquid-phase high-temperature decomposition to obtain metal sulfide nanocircles. Nanocircles can eliminate the influence of stress, that is, the material itself has deformation and can be deformed, so as to better sense the detected signal. In addition, nanocircles with metallic characteristics not only have strain tolerance, but also have excellent conductivity, which improves the stretchability of the material and increases the charge transfer capacity, thereby effectively improving the sensitivity and stability of the sensor. Summary of the invention

[0005] The invention aims to disclose a Sn0.2 Mo 0.8 S 2 The invention uses SnS nanospheres as sensing materials in flexible pressure sensors and temperature sensors. 2 Nanosheets, Sn 0.3 Mo 0.7 O 3 Nanorods and thiourea were used as reaction precursors to prepare Sn 0.2 Mo 0.8 S 2 Then, the nanocircles are sprayed on the interdigital electrodes and dried to form a film to prepare a chemical resistance pressure sensor and a temperature sensor. 0.2 Mo 0.8 S 2 Nanosphere nanomaterials have high sensitivity and stability, and can monitor motion signals, physiological signals and temperature signals.

[0006] In order to solve the technical problem of the present invention, the proposed technical solution is: a Sn 0.2 Mo 0.8 S 2 The application of nanospheres is characterized by: Sn 0.2 Mo 0.8 S 2 Nanospheres can be used in pressure sensing and temperature sensing materials and devices.

[0007] The Sn 0.2 Mo 0.8 S 2 The nanosphere preparation method is as follows:

[0008] (1) Take 175.3 mg SnCl 4 ·5H 2 O and 640 mg CS(NH 2 ) 2 After being dissolved in 40 mL of deionized water, the mixture was transferred to a 50 mL polytetrafluoroethylene high-pressure hydrothermal reactor. The reactor was then placed in an oven at 220°C for 12 h, and then naturally cooled to room temperature before being taken out. The obtained product was centrifuged, washed, and stored in deionized water to obtain SnS2 nanosheets.

[0009] (2) Take 497 mg (NH 4 ) 6 Mo 7 O 24 ·4H 2 O and 173 mg SnCl 4 ·5H 2O was dissolved in 20 mL of deionized water and then transferred to a hydrothermal autoclave with a capacity of 25 mL of a polytetrafluoroethylene liner doped with para-polyphenol; the autoclave was then placed in an oven at 220°C for 12 h, and then naturally cooled to room temperature and taken out; the obtained product was centrifuged, washed, and stored in deionized water to obtain Sn 0.3 Mo 0.7 O 3 Nanorods;

[0010] (3) Take 1.2 mg Sn 0.3 Mo 0.7 O 3 Nanorods, 60mg SnS 2 Nanosheets, 0.32 g CS(NH 2 ) 2 and 19 mL of deionized water and then transferred to a 25 mL polytetrafluoroethylene high-pressure hydrothermal reactor; the reactor was then placed in an oven at 240 ° C for 60 h, and then naturally cooled to room temperature and taken out; the obtained product Sn 0.2 Mo 0.8 S 2 The nanospheres were centrifuged, washed, and stored in deionized water for later use;

[0011] The Sn 0.2 Mo 0.8 S 2 Nanospheres can be used for the application of pressure sensing materials and devices, and the steps are as follows:

[0012] (1) Two sizes of silver interdigital electrodes were printed on PET film by inkjet printing. Electrode 1 was 18.72 mm long, 8.24 mm wide, 0.32 mm interdigital spacing, 0.32 mm line width, 0.1 mm substrate thickness, and the overall size of the sensor was 18.24 × 28.72 mm. In order to test vital signs on the skin, the size of the interdigital electrodes was reduced. Electrode 2 was prepared to be 11.20 mm long, 5.63 mm wide, 0.32 mm interdigital spacing, 0.36 mm line width, 0.0125 mm substrate thickness, and the overall size of the sensor was 15.63 × 21.20 mm. The wires were connected to the two ends of the electrodes by silver glue and dried at room temperature for one day. A certain amount of Sn was then sprayed on the skin using an airbrush (with a diameter of 0.3 mm). 0.2 Mo 0.8 S 2 The nanospheres were uniformly sprayed on the surface of the interdigitated electrodes, with a thickness of about 20 to 50 μm. The spraying process was completed on a 35°C heating table to allow the solvent to evaporate quickly, and care should be taken to expose both ends of the electrode during spraying. The flexible pressure sensor was then dried in a vacuum drying oven at 60°C for 1 hour.

[0013] The Sn 0.2 Mo0.8 S 2 Nanospheres can be used for applications in temperature sensing materials and devices, and the steps are as follows:

[0014] (1) Use a microelectronic printer to print No. 1 PET interdigital electrodes on the PET film: length 18.72 mm, width 8.24 mm, finger spacing 0.32 mm, line width 0.32 mm, substrate thickness 0.1 mm, the overall size of the sensor is 18.24×28.72 mm;

[0015] (2) After printing, fix the two copper wires on the Ag IDE through conductive silicone and fix the Sn 0.2 Mo 0.8 S 2 Nanospheres were sprayed on the surface of Ag IDE to prepare a flexible temperature sensor. Finally, the corresponding changes in the sensor's electrical signal were monitored and recorded by a data acquisition system.

[0016] Preferably, the Sn 0.2 Mo 0.8 S 2 Applications of Nanospheres:

[0017] (1) Use a stretching device (stepping motor) to test the response of the sensor under different bending conditions; fix sensor No. 1 on the stretching device, connect the sensor to the data logger through a wire, and adjust the position of the stretching device's motion clamp so that the sensor is in the horizontal, unbent initial state (baseline resistance R 0 ); input the cycle program, and realize the reciprocating process of the sensor from non-bending to bending by controlling the moving end of the stretching device to do the cyclic reciprocating motion of stretching and bending; the compression length of the sensor is ΔL = 0.05mm, 0.1mm, 0.2mm, 0.4mm, 0.6mm, and each length is cycled ten times; the resistance of the sensor when it is bent is recorded as R, and the response of the pressure sensor is (RR 0 ) / R 0 ; Collect the electrical signals of the sensor during the cycle through the data acquisition device to obtain the relationship between resistance and time;

[0018] (2) Fit sensor No. 2 to the body part and connect it to the data collector with a wire to test the movement response and physiological response; fit the sensor tightly to the finger joints, wrist joints and throat respectively, and then collect the data of electrical signals through the data collector during the process of bending the fingers, bending the wrists, swallowing and shaking the head; the resistance of the sensor when not moving is recorded as R 0 The resistance during the above action is recorded as R, so its response size is (RR 0 ) / R 0; Fit sensor No. 2 tightly to the throat and wrist respectively, and test the physiological responses produced by normal breathing and deep breathing, reading the word "sensor" and pulse beating; collect electrical data by a data logger or electrochemical workstation.

[0019] Preferably, the Sn 0.2 Mo 0.8 S 2 Application of Nanospheres, the Sn 0.2 Mo 0.8 S 2 The nanospheres are sprayed on the interdigital electrodes and dried to form a film, and then prepared into a chemical resistance sensor that can simultaneously monitor pressure and temperature. 0.2 Mo 0.8 S 2 Nanosphere nanomaterials not only have high sensitivity and stability, but can also be used in flexible sensing to monitor important human vital signs such as pulse and breathing.

[0020] In order to solve the technical problem of the present invention, the proposed technical solution is: a pressure sensing material based on a two-dimensional transition metal chalcogenide nanostructure, according to the Sn according to claim 1 0.2 Mo 0.8 S 2 Nanosphere pressure sensing materials are used to prepare pressure sensor devices.

[0021] In order to solve the technical problem of the present invention, the proposed technical solution is: a temperature sensing material based on a two-dimensional transition metal chalcogenide nanostructure, according to the Sn according to claim 1 0.2 Mo 0.8 S 2 Nanosphere temperature sensing materials are used to prepare temperature sensing devices.

[0022] Beneficial effects:

[0023] This invention realizes the construction of Sn by hydrothermal method for the first time. 0.2 Mo 0.8 S 2 Nanocircles are used for the first time as pressure and temperature sensitive materials in flexible pressure sensors and temperature sensors with high sensitivity and good stability.

[0024] For a single-function sensor, the present invention converts Sn 0.2 Mo 0.8 S 2 The nanospheres are sprayed on the interdigital electrodes and dried to form a film, and then prepared into a chemical resistance sensor that can simultaneously monitor pressure and temperature. Most importantly, the Sn 0.2 Mo 0.8 S2 Nanosphere nanomaterials not only have high sensitivity and stability, but can also be used in flexible sensing to monitor important human vital signs such as pulse and breathing.

[0025] like Figure 6 As shown, based on Sn 0.2 Mo 0.8 S 2 The photos and pressure response-recovery curves of the pressure sensor made of nanospheres bent into different radii (r = 150, 106, 75, 53, 43.2 mm, corresponding to unilateral steps of 0.05, 0.1, 0.2, 0.4, 0.6 mm) ten times. As the bending radius decreases, the response value of the sensor increases. In addition, the Sn of the nanosphere structure 0.2 Mo 0.8 S 2 It has a slight deformable property, ensuring Sn 0.2 Mo 0.8 S 2 Stability of the nanosphere pressure sensor.

[0026] Currently, there is almost no SnS 2 The SnS prepared by us has been reported for pressure sensing and temperature sensing. 2 Flexible sensor, at a certain concentration, when SnS 2 When the amount of nanosheet spraying is small, a large number of cracks in the sensing layer film seriously hinder the charge transfer, resulting in SnS 2 The flexible sensor cannot be turned on. Although the amount of spraying is increased, SnS 2 Flexible sensors can achieve conduction, but the sensing layer film is thicker, the flexibility of the film decreases, and the rigidity increases, which makes the film easy to break when the sensor is bent. 2 Nanosheets are not suitable as stress and temperature sensing materials.

[0027] The Sn 0.2 Mo 0.8 S 2 The nanocircle flexible sensor can achieve flexible sensing in multiple ways such as bending fingers, bending wrists, swallowing, shaking heads, etc., and has good sensitivity and stability. 2 Nanosheets transform into Sn 0.2 Mo 0.8 S 2 After the nanocircle, not only temperature and pressure sensing can be realized, but also pressure and temperature sensing in a flexible state can be realized.

[0028] Sn 0.2 Mo 0.8 S 2The nanosphere sensor showed a fast response time (13 seconds) and recovery time (6 seconds). The Sn was tested by cyclic tests of heating to 50°C and cooling to 21°C. 0.2 Mo 0.8 S 2 Excellent temperature discrimination capability, small display deviation, thus good stability and repeatability.

[0029] Sn prepared by the present invention 0.2 Mo 0.8 S 2 The sensitivity of the nanosphere temperature sensor is -0.013°C -1 , the temperature sensing range is 25-85°C. Compared with the sensors listed in Table 1, the sensing sensitivity of the temperature sensors based on several inorganic materials is not high, which is lower than that of the Sn prepared by the present invention. 0.2 Mo 0.8 S 2 Nanocircle sensor. In addition, the manufacturing methods used in the sensors in Table 1 are relatively complicated. 0.2 Mo 0.8 S 2 The nanosphere sensor is superior to other sensor preparation methods in terms of preparation methods. 0.2 Mo 0.8 S 2 The nanosphere solution is uniformly sprayed on the interdigital electrodes and dried to obtain the desired sensor for subsequent detection of changes in pressure and temperature signals.

[0030] Sn prepared by the present invention 0.2 Mo 0.8 S 2 The sensitivity of the nanocircle pressure sensor is 558, the stress sensing range is 0.03%-0.5%, and the minimum detectable stress is 0.03%. 0.2 Mo 0.8 S 2 The minimum detectable stress of the nanosphere stress sensor is much better than that of the stress sensors listed in Table 2. In addition, the manufacturing methods used for the sensors in Table 2 are relatively complicated. 0.2 Mo 0.8 S 2 The nanosphere sensor is superior to other sensor preparation methods in terms of preparation methods. 0.2 Mo 0.8 S 2 The nanosphere solution is uniformly sprayed on the interdigital electrodes and dried to obtain the desired sensor for subsequent detection of changes in pressure and temperature signals. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1is Sn in Example 1 0.2 Mo 0.8 S 2 SEM image of the nanosphere.

[0032] Figure 2 is Sn in Example 1 0.2 Mo 0.8 S 2 EDX surface scan of the nanosphere.

[0033] Figure 3 is Sn in Example 1 0.2 Mo 0.8 S 2 XPS pattern of Sn 3d in the nanosphere.

[0034] Figure 4 is Sn in Example 1 0.2 Mo 0.8 S 2 XPS pattern of Mo 3d in the nanosphere.

[0035] Figure 5 is Sn in Example 1 0.2 Mo 0.8 S 2 XPS pattern of S 2p in the nanosphere.

[0036] Figure 6 Based on Sn in Example 4 0.2 Mo 0.8 S 2 Actual photos and pressure response-recovery curves of the pressure sensor prepared by nanocircles bent into different radii (r=150, 106, 75, 53, 43.2 mm, corresponding to single-sided steps of 0.05, 0.1, 0.2, 0.4, 0.6 mm) ten times.

[0037] Figure 7 Based on Sn in Example 4 0.2 Mo 0.8 S 2 Motion sensing test of the nanocircle pressure sensor when the finger is bent at 45°.

[0038] Figure 8 Based on Sn in Example 4 0.2 Mo 0.8 S 2 Motion sensing test of the nanocircle pressure sensor with the wrist bent at 90°.

[0039] Fig. 9 Based on Sn in Example 4 0.2 Mo 0.8 S 2 Testing of the nanosphere pressure sensor for motion sensing during swallowing.

[0040] Fig.10 Based on Sn in Example 4 0.2 Mo 0.8 S 2 Motion sensing test of the nanocircle pressure sensor when shaking the head. Fig.11 Based on Sn in Example 5 0.2 Mo 0.8 S 2 Sensing test of the nanosphere sensor detecting breathing (normal breathing and deep breathing).

[0041] Fig.12 Based on Sn in Example 5 0.2 Mo 0.8 S 2 Sound sensing test of the Nanosphere sensor detecting the repeated word "sensor".

[0042] Fig.13 Based on Sn in Example 5 0.2 Mo 0.8 S 2 Sensing test of nanosphere sensor detecting pulse.

[0043] Fig.14 In Example 6, the flexible Sn 0.2 Mo 0.8 S 2 The electrical response of the nanosphere temperature sensor changes with temperature.

[0044] Fig.15 In Example 6, the flexible Sn 0.2 Mo 0.8 S 2 Electrical response of the nanosphere temperature sensor in the temperature range of 30–65 °C.

[0045] Fig.16 In Example 6, the flexible Sn 0.2 Mo 0.8 S 2 The nanosphere temperature sensor calculates the temperature coefficient of resistance as the temperature sensitivity.

[0046] Fig.17 In Example 6, the flexible Sn 0.2 Mo 0.8 S 2 Response and recovery time of the nanosphere temperature sensor. Fig.18 In Example 6, the flexible Sn 0.2 Mo 0.8 S 2 The temperature discrimination capability of the Nanosphere temperature sensor measured at 21°C and 50°C. DETAILED DESCRIPTION

[0047] In order to better understand the present invention, the technical solution of the present invention is specifically described below through specific embodiments in conjunction with the accompanying drawings.

[0048] Example 1: Preparation of Sn by wet chemical method 0.2 Mo 0.8 S 2 Nanosphere

[0049] (1) 175.3 mg SnCl 4 ·5H 2 O and 640 mg CS(NH 2 ) 2 After being dissolved in 40 mL of deionized water, it was transferred to a 50 mL polytetrafluoroethylene high-pressure hydrothermal reactor. The reactor was then placed in an oven at 220°C for 12 hours, and then naturally cooled to room temperature before being taken out. The obtained product was centrifuged at a speed of 9000 r / min for 10 minutes, and the centrifuged product was washed 3-4 times with deionized water and stored in 10 mL of deionized water to obtain SnS 2 Nanosheets;

[0050] (2) Take 497 mg (NH 4 ) 6 Mo 7 O 24 ·4H 2 O and 173 mg SnCl 4 ·5H 2 O was dissolved in 20 mL of deionized water and transferred to a 25 mL polytetrafluoroethylene high pressure hydrothermal reactor. The reactor was then placed in an oven at 220 °C for 12 h, cooled to room temperature and then taken out. The obtained product was centrifuged, washed, and stored in deionized water to obtain Sn 0.3 Mo 0.7 O 3 Nanorods;

[0051] (3) Take 1.2 mg Sn 0.3 Mo 0.7 O 3 Nanorods, 60mg SnS 2 Nanosheets, 0.32 g CS(NH 2 ) 2 After adding 19 mL of deionized water, the mixture was transferred to a 25 mL polytetrafluoroethylene high pressure hydrothermal reactor. The reactor was then placed in an oven at 240°C for 60 h, cooled to room temperature, and then taken out. The obtained product was centrifuged, washed, and stored in deionized water for later use to obtain Sn. 0.2 Mo 0.8 S 2 .

[0052] For the product Sn in Example 1 0.2 Mo 0.8 S 2 Perform analysis such as Figure 1 As shown, Sn 0.2 Mo 0.8 S 2 The SEM image shows that the final Sn 0.2 Mo 0.8 S 2 It is a nanosphere structure.

[0053] like Figure 2 As shown, Sn 0.2 Mo 0.8 S 2 In the EDX scan of the nanosphere, Sn, Mo and S are mainly distributed at the edge of the framework structure, and there is no distribution of these three elements inside, which proves that the formed nanosphere is Sn. 0.2 Mo 0.8 S 2 , indicating Sn 0.2 Mo 0.8 S 2 Located at the edge of the hollow structure, SnS 2 The hexagonal nanosheets have been completely etched, which further proves that Sn 0.2 Mo 0.8 S 2 The morphology is a nanocircle structure with a hollow interior.

[0054] like Figure 3 As shown, Sn 0.2 Mo 0.8 S 2 XPS graph of Sn 3d in the nanosphere. In the Sn 3d spectrum, Sn 3d 3 / 2 Tracks and Sn 3d 5 / 2 The peak of the orbital is similar to that of 1T-SnS 2 The structures match perfectly. The peaks at 494.1eV and 485.7eV correspond to Sn3d 3 / 2 and Sn 3d 5 / 2 Spin state.

[0055] like Figure 4 As shown, Sn 0.2 Mo 0.8 S 2 XPS graph of Mo 3d in the nanosphere. In the Mo 3d spectrum, the peak positions are 231.8eV, 228.5eV and 225.5eV, which correspond to the Mo3d 3 / 2 and Mo 3d 5 / 2The spin state and S 2s overlap region, with a double peak spacing of 3.3 eV. The Mo 3d narrow spectrum was analyzed by peak separation, and the 1T phase Mo 4+ The binding energies of the corresponding peaks are 231.8eV and 228.5eV, and the 2H phase Mo 4+ The binding energies of the corresponding peaks are 232.8eV and 229.5eV respectively. 4+ The binding energy of the corresponding peak, 1T phase Mo 4+ The binding energy of the corresponding peak decreased by 1 eV. 0.2 Mo 0.8 S 2 The existence of 1T phase Mo-S coordination in the Sn phase can be quantitatively estimated by calculating the area ratio of the corresponding peaks between different phases of Mo element. 0.2 Mo 0.8 S 2 The relative content of 1T phase and 2H phase in the Sn 0.2 Mo 0.8 S 2 The relative contents of 1T phase and 2H phase are 80% and 20%, respectively.

[0056] like Figure 5 As shown, Sn 0.2 Mo 0.8 S 2 XPS graph of S 2p in the nanosphere. In the S 2p spectrum, the peaks at 162.0eV and 160.7eV correspond to the S 2p of the S element, respectively. 1 / 2 and S 2p 3 / 2 Spin state. It is confirmed that Sn 0.2 Mo 0.8 S 2 The existence of Sn-S coordination in the 1T phase.

[0057] Example 2

[0058] The first set of experiments:

[0059] (1) Take 175.3 mg SnCl 4 ·5H 2 O and 640 mg CS(NH 2 ) 2 After being dissolved in 40 mL of deionized water, it was transferred to a 50 mL polytetrafluoroethylene high-pressure hydrothermal reactor. The reactor was then placed in an oven at 220°C for 12 h, and then naturally cooled to room temperature before being taken out. The obtained product was centrifuged, washed, and stored in deionized water to obtain SnS 2 Nanosheets;

[0060] (2) Take 497 mg (NH 4 ) 6 Mo7 O 24 ·4H 2 O and 173 mg SnCl 4 ·5H 2 O was dissolved in 20 mL of deionized water and transferred to a 25 mL polytetrafluoroethylene high pressure hydrothermal reactor. The reactor was then placed in an oven at 200 °C for 12 h, cooled to room temperature and then taken out. The obtained product was centrifuged, washed, and stored in deionized water to obtain Sn 0.3 Mo 0.7 O 3 Nanorods;

[0061] (3) Take 1.2 mg Sn 0.3 Mo 0.7 O 3 Nanorods, 60mg SnS 2 Nanosheets, 0.32 g CS(NH 2 ) 2 and 19 mL of deionized water and then transferred to a 25 mL polytetrafluoroethylene high pressure hydrothermal reactor. The reactor was then placed in an oven at 240°C for 30 h, cooled naturally to room temperature and then taken out. The obtained product was centrifuged, washed, and stored in deionized water for later use.

[0062] For the product Sn in Example 2 0.2 Mo 0.8 S 2 For analysis, Sn 0.2 Mo 0.8 S 2 The nanosphere has been generated, but the SnS 2 It has not been completely etched yet, and some SnS inside 2 Nanosheets can have a negative impact on subsequent pressure sensing.

[0063] The second set of experiments:

[0064] (1) Take 175.3 mg SnCl 4 ·5H 2 O and 640 mg CS(NH 2 ) 2 After being dissolved in 40 mL of deionized water, it was transferred to a 50 mL polytetrafluoroethylene high-pressure hydrothermal reactor. The reactor was then placed in an oven at 220°C for 12 h, and then naturally cooled to room temperature before being taken out. The obtained product was centrifuged, washed, and stored in deionized water to obtain SnS 2 Nanosheets;

[0065] (2) Take 497 mg (NH 4 ) 6 Mo7 O 24 ·4H 2 O and 173 mg SnCl 4 ·5H 2 O was dissolved in 20 mL of deionized water and then transferred to a 25 mL polytetrafluoroethylene high-pressure hydrothermal reactor. The reactor was then placed in an oven at 180 °C for 12 h, cooled to room temperature, and then taken out. The obtained product was washed with deionized water three times to obtain Sn 0.3 Mo 0.7 O 3 Nanorods.

[0066] (3) Take 1.2 mg Sn 0.3 Mo 0.7 O 3 Nanorods, 60mg SnS 2 Nanosheets, 0.32 g CS(NH 2 ) 2 and 19 mL of deionized water and then transferred to a 25 mL polytetrafluoroethylene high pressure hydrothermal reactor. The reactor was then placed in an oven at 220°C for 30 h, cooled naturally to room temperature and then taken out. The obtained product was centrifuged, washed, and stored in deionized water for later use.

[0067] The product Sn 0.2 Mo 0.8 S 2 For analysis, Sn 0.2 Mo 0.8 S 2 SnS in the middle of the nanosphere 2 The nanosphere framework has not been completely formed yet, and the SnS 2 The presence of stress has a negative impact on subsequent pressure sensing.

[0068] Example 3: Sn 0.2 Mo 0.8 S 2 Sensor Application—Pressure Sensing Test

[0069] (1) Take the Sn prepared in Example 1 0.2 Mo 0.8 S 2Nanocircle solution, two sizes of silver interdigital electrodes were printed on PET film using inkjet printing, electrode No. 1: 18.72mm long, 8.24mm wide, 0.32mm finger spacing, 0.32mm line width, 0.1mm substrate thickness, the overall size of the sensor is 18.24×28.72mm; in order to be able to test on the skin, the size of the interdigital electrode was reduced, and electrode No. 2 was prepared: 11.20mm long, 5.63mm wide, 0.32mm finger spacing, 0.36mm line width, 0.0125mm substrate thickness, the overall size of the sensor is 15.63×21.20mm. The wire was connected to both ends of the electrode with silver glue and dried at room temperature for one day. Then a certain amount of Sn was sprayed with an airbrush (caliber 0.3mm) 0.2 Mo 0.8 S 2 Evenly spray on the surface of the interdigital electrode, the thickness of the nanosphere is about 20-50μm. The spraying process is completed on a 35℃ heating table to allow the solvent to evaporate quickly. When spraying, care should be taken to expose both ends of the electrode. Dry at 60℃ in vacuum for 1h to obtain a flexible pressure sensor.

[0070] (2) Use a stretching device (stepper motor) to test the response of the sensor under different bending conditions. Fix sensor No. 1 on the stretching device, connect the sensor to the data logger through a wire, and adjust the position of the stretching device's motion clip so that the sensor is in the horizontal, unbent initial state (baseline resistance R 0 ). Input the cycle program, and control the moving end of the stretching device to perform a cyclic reciprocating motion of stretching and bending to realize the reciprocating process of the sensor from non-bending to bending. The compression lengths of the sensor are ΔL = 0.05mm, 0.1mm, 0.2mm, 0.4mm, and 0.6mm, respectively, and each length is cycled ten times. The resistance of the sensor when it is bent is recorded as R, and the response of the pressure sensor is (RR 0 ) / R 0 The electrical signal of the sensor during the cycle is collected by a data logger to obtain a relationship diagram between resistance and time;

[0071] (3) Fit sensor No. 2 to the body part and connect it to the data collector with a wire to test the movement response and physiological response. Fit the sensor tightly to the finger joints, wrist joints and throat respectively, and then collect the data of electrical signals through the data collector during the process of bending the fingers, bending the wrists, swallowing and shaking the head. The resistance of the sensor when not moving is recorded as R 0 The resistance during the above action is recorded as R, so its response size is (RR 0 ) / R 0. Fit sensor No. 2 to the throat and wrist respectively, and test the physiological responses produced by normal breathing and deep breathing, reading the word "sensor" and pulse beating. Collect electrical data by data acquisition or electrochemical workstation.

[0072] like Figure 6 As shown, based on Sn 0.2 Mo 0.8 S 2 Photos of the pressure sensor made of nanocircles bent into different radii ten times and the pressure response-recovery curve. When PET is bent upward, Sn 0.2 Mo 0.8 S 2 The resistance of the sensor increases, showing a positive response. As the bending radius decreases, the response value of the sensor increases. In the reverse bending, Sn 0.2 Mo 0.8 S 2 The sensors showed the opposite.

[0073] Figure 7 Sn 0.2 Mo 0.8 S 2 The motion sensing of the nanocircle pressure sensor is tested when the finger is bent at 45°. It can be seen that when the finger is bent, the sensor bends positively, the resistance increases, and it shows a positive response with a large response value (60%). In addition, we also observed that the response value of the pressure sensor is basically the same when the finger is bent and stretched 25 times, indicating that Sn 0.2 Mo 0.8 S 2 The sensor has good repeatability.

[0074] Figure 8 Sn 0.2 Mo 0.8 S 2 The motion sensing of the nanocircle pressure sensor was tested at a 90° wrist bend, detecting the change in resistance of the sensor when the wrist was straightened and bent 90°.

[0075] Fig. 9 Sn is shown when swallowing. 0.2 Mo 0.8 S 2 The response curve of the nanocircle sensor over time. From the figure, we can see that there are two adjacent peaks when swallowing, which correspond to the rise and fall of the Adam's apple during swallowing, and the response value is about 25%.

[0076] Fig.10In order to detect the slight expansion and contraction changes of the neck skin when shaking the head to identify the shaking head movement, it can be seen that the head is quickly turned from the left to the right, paused for 3 seconds, then quickly turned from the right back to the left, and paused for 3 seconds, and this cycle is repeated 9 times to measure the response time relationship curve of the shaking head movement. In the process of the head quickly turning from one side to the other, the neck skin undergoes a state of stretching-relaxing-stretching. When the skin stretches, it causes the sensor Sn to 0.2 Mo 0.8 S 2 The film generates a small amount of pressure, Sn 0.2 Mo 0.8 S 2 The number of contact channels between nanocircles decreases, the carrier transport efficiency decreases, so the resistance increases and the response value increases.

[0077] Example 4: Sn 0.2 Mo 0.8 S 2 Application of sensors - monitoring of vital signs

[0078] (1) Take the Sn prepared in Example 1 0.2 Mo 0.8 S 2 Nanosphere solution, using inkjet printing to print silver interdigital electrodes on PET film. Connect the wires to both ends of the electrodes with silver glue and dry them at room temperature for one day. Then use an airbrush (caliber 0.3mm) to spray a certain amount of Sn 0.2 Mo 0.8 S 2 The nanospheres were evenly sprayed on the surface of the interdigitated electrodes, with a thickness of about 20 to 50 μm. The spraying process was completed on a 35°C heating table to allow the solvent to evaporate quickly. During the spraying process, care should be taken to expose both ends of the electrode. The flexible pressure sensor for monitoring vital signs was obtained by vacuum drying at 60°C for 1 hour.

[0079] (2) Sn 0.2 Mo 0.8 S 2 The sensor fits tightly against the skin at the throat to detect the respiratory rate. (3) 0.2 Mo 0.8 S 2 The sensor is placed against the throat and detects the vibration of the vocal cords when the word "sensor" is spoken.

[0080] (4) Sn 0.2 Mo 0.8 S 2 The sensor fits snugly against the skin at the pulse location and is used to observe the frequency, waveform and intensity of radial artery pressure to monitor / diagnose conditions such as arterial stiffness and hypertension.

[0081] Fig.11Sn 0.2 Mo 0.8 S 2 Nanocircle sensor detection breathing sensor test, real-time detection of normal breathing and deep breathing of healthy men in a calm state, Sn 0.2 Mo 0.8 S 2 The resistance of the pressure sensor increases, and the resistance decreases when exhaling. The results show that under normal breathing conditions, the number of breaths in one minute is 15, the breathing cycle is 4s, the intensity is consistent, and the breathing is even, which is within the normal range of healthy men; under deep breathing conditions, the number of breaths in one minute is 10, the breathing cycle is 6s, the breathing is even, the intensity is consistent, and it is within the normal range.

[0082] Fig.12 Sn 0.2 Mo 0.8 S 2 The nanocircle sensor detected the vibration signal when the word "sensor" was repeatedly spoken. It was observed that the signal waveform was basically the same each time the word was read aloud, and the intensity and vibration time were basically the same, which showed repeatability and distinguishability. 0.2 Mo 0.8 S 2 The sensor has great potential for application in intelligent speech recognition and speech correction exercises.

[0083] Fig.13 Sn 0.2 Mo 0.8 S 2 The nanocircle sensor measures the real-time pulse signal of a 25-year-old healthy male in a calm state. It can be observed that the male's pulse beats 12 times in ten seconds, which is an average of 72 times per minute, which is within the normal range of a healthy male (60-100 times per minute). It can also be seen that the signal value generated by each pulse beat is at the same level (about 0.011×10 -6 mA), indicating that the man's pulse strength is stable.

[0084] Example 5: Sn 0.2 Mo 0.8 S 2 Sensor Application—Temperature Sensing Test

[0085] (1) Take a certain amount of Sn prepared in Example 1 0.2 Mo 0.8 S 2 The solution was sprayed evenly on the conductive Ag interdigitated electrodes (Ag IDE) with a spacing of 0.3 mm, exposing only the electrodes at both ends of the gold interdigitated electrodes, and then dried in vacuum at 60 °C for one day;

[0086] (2) Finally, the corresponding changes in the sensor electrical signal are monitored and recorded through the data acquisition system.

[0087] Fig.14 The resistance of the temperature sensor changes with temperature. It can be seen that the resistance of the temperature sensor decreases as the temperature increases, showing a negative temperature coefficient (NTC).

[0088] Fig.15 Fitting Sn 0.2 Mo 0.8 S 2 Response curves of the nanosphere temperature sensor to different temperatures.

[0089] Fig.16 The temperature coefficient of resistance is calculated as the temperature sensitivity for the temperature sensor. The linear curve fitting obtained calculates the temperature coefficient of resistance to be -0.013℃ -1 .

[0090] Fig.17 Sn 0.2 Mo 0.8 S 2 Response and recovery time of temperature sensor, Sn 0.2 Mo 0.8 S 2 The nanosphere sensor showed fast response time (13 seconds) and recovery time (6 seconds).

[0091] Fig.18 Sn was tested by cyclic test with heating to 50°C and cooling to 21°C 0.2 Mo 0.8 S 2 Excellent temperature discrimination capability, small display deviation, thus good stability and repeatability.

[0092] Comparative Example 1

[0093] Currently, there is almost no SnS 2 The SnS prepared by us has been reported for pressure sensing and temperature sensing. 2 Flexible sensor, at a certain concentration, when SnS 2 When the amount of nanosheet spraying is small, a large number of cracks in the sensing layer film seriously hinder the charge transfer, resulting in SnS 2 The flexible sensor cannot be turned on. Although the amount of spraying is increased, SnS 2 Flexible sensors can achieve conduction, but the sensing layer film is thicker, the flexibility of the film decreases, and the rigidity increases, which makes the film easy to break when the sensor is bent. 2 Nanosheets are not suitable as stress and temperature sensing materials.

[0094] The Sn 0.2Mo 0.8 S 2 The nanocircle flexible sensor can achieve flexible sensing in multiple ways such as bending fingers, bending wrists, swallowing, shaking heads, etc., and has good sensitivity and stability. 2 Nanosheets transform into Sn 0.2 Mo 0.8 S 2 After the nanocircle, not only temperature and pressure sensing can be realized, but also pressure and temperature sensing in a flexible state can be realized.

[0095] Comparative Example 2

[0096] Sn prepared by the present invention 0.2 Mo 0.8 S 2 The sensitivity of the nanosphere temperature sensor is -0.013°C -1 , the temperature sensing range is 25-85°C. Compared with the sensors listed in Table 1, the sensing sensitivity of the temperature sensors based on several inorganic materials is not high, which is lower than that of the Sn prepared by the present invention. 0.2 Mo 0.8 S 2 Nanocircle sensor. In addition, the manufacturing methods used in the sensors in Table 1 are relatively complicated. 0.2 Mo 0.8 S 2 The nanosphere sensor is superior to other sensor preparation methods in terms of preparation methods. 0.2 Mo 0.8 S 2 The nanosphere solution is uniformly sprayed on the interdigital electrodes and dried to obtain the desired sensor for subsequent detection of changes in pressure and temperature signals.

[0097] Table 1

[0098]

[0099]

[0100] Comparative Example 3

[0101] Sn prepared by the present invention 0.2 Mo 0.8 S 2 The sensitivity of the nanocircle pressure sensor is 558, the stress sensing range is 0.03%-0.5%, and the minimum detectable stress is 0.03%. 0.2 Mo 0.8 S 2The minimum detectable stress of the nanosphere stress sensor is much better than that of the stress sensors listed in Table 2. In addition, the manufacturing methods used for the sensors in Table 2 are relatively complicated. 0.2 Mo 0.8 S 2 The nanosphere sensor is superior to other sensor preparation methods in terms of preparation methods. 0.2 Mo 0.8 S 2 The nanosphere solution is uniformly sprayed on the interdigital electrodes and dried to obtain the desired sensor for subsequent detection of changes in pressure and temperature signals.

[0102] Table 2

[0103]

Claims

1. A Sn 0.2 Mo 0.8 The application of S2 nanosphere is characterized by: Sn 0.2 Mo 0.8 S2 nanospheres can be used in the application of pressure sensing and temperature sensing materials and devices. The Sn 0.2 Mo 0.8 The preparation method of S2 nanosphere is as follows: (1) 175.3 mg SnCl4·5H2O and 640 mg CS(NH2)2 were dissolved in 40 mL deionized water and then transferred to a 50 mL polytetrafluoroethylene high-pressure hydrothermal reactor; the reactor was then placed in an oven at 220°C for 12 h, cooled naturally to room temperature and then taken out; the obtained product was centrifuged, washed, and stored in deionized water to obtain SnS2 nanosheets; (2) Take 497 mg (NH4)6Mo7O 24 ·4H2O and 173mg SnCl4·5H2O were dissolved in 20mL deionized water and transferred to a hydrothermal autoclave with a capacity of 25mL of a polytetrafluoroethylene liner doped with para-polyphenol; the autoclave was then placed in an oven at 220°C for 12h, cooled naturally to room temperature and then taken out; the obtained product was centrifuged, washed, and stored in deionized water to obtain Sn 0.3 Mo 0.7 O3 nanorods; (3) Take 1.2 mg Sn 0.3 Mo 0.7 O3 nanorods, 60 mg SnS2 nanosheets, 0.32 g CS(NH2)2 and 19 mL deionized water were transferred to a 25 mL polytetrafluoroethylene high pressure hydrothermal reactor; the reactor was then placed in an oven at 240 °C for 60 h, cooled naturally to room temperature and then taken out; the obtained product Sn 0.2 Mo 0.8 S2 nanospheres were centrifuged, washed, and stored in deionized water for later use; The Sn 0.2 Mo 0.8 S2 nanospheres can be used for the application of pressure sensing materials and devices, and the steps are as follows: (1) Two sizes of silver interdigital electrodes were printed on PET film by inkjet printing. Electrode 1 was 18.72 mm long, 8.24 mm wide, 0.32 mm interdigital spacing, 0.32 mm line width, 0.1 mm substrate thickness, and the overall size of the sensor was 18.24 × 28.72 mm. In order to test vital signs on the skin, the size of the interdigital electrodes was reduced. Electrode 2 was prepared to be 11.20 mm long, 5.63 mm wide, 0.32 mm interdigital spacing, 0.36 mm line width, 0.0125 mm substrate thickness, and the overall size of the sensor was 15.63 × 21.20 mm. The wires were connected to the two ends of the electrodes by silver glue and dried at room temperature for one day. A certain amount of Sn was then sprayed on the skin using an airbrush (with a diameter of 0.3 mm). 0.2 Mo 0.8 S2 was evenly sprayed on the surface of the interdigital electrode, and the thickness of the nanocircle was about 20 to 50 μm. The spraying process was completed on a 35°C heating table to allow the solvent to evaporate quickly. During the spraying process, care should be taken to expose both ends of the electrode. The electrode was then dried in a vacuum drying oven at 60°C for 1 hour to obtain a flexible pressure sensor. The Sn 0.2 Mo 0.8 S2 nanospheres can be used for applications in temperature sensing materials and devices, and the steps are as follows: (1) Use a microelectronic printer to print No. 1 PET interdigital electrodes on the PET film: length 18.72 mm, width 8.24 mm, finger spacing 0.32 mm, line width 0.32 mm, substrate thickness 0.1 mm, the overall size of the sensor is 18.24×28.72 mm; (2) After printing, fix the two copper wires on the Ag IDE through conductive silicone and fix the Sn 0.2 Mo 0.8 S2 nanocircles were sprayed on the surface of Ag IDE to prepare a flexible temperature sensor; finally, the corresponding changes in the sensor's electrical signal were monitored and recorded by a data acquisition system.

2. Sn according to claim 1 0.2 Mo 0.8 The application of S2 nanosphere is characterized by: (1) Use a stretching device (stepping motor) to test the response of the sensor under different bending states; fix sensor No. 1 on the stretching device, connect the sensor to the data acquisition device through a wire, and adjust the position of the stretching device motion clamp so that the sensor is in the initial state of horizontal non-bending (baseline resistance R0); Input the cycle program, and realize the reciprocating process of the sensor from non-bending to bending by controlling the moving end of the stretching device to perform a cyclic reciprocating motion of stretching and bending; the compression lengths of the sensor are ΔL=0.05mm, 0.1mm, 0.2mm, 0.4mm, and 0.6mm, respectively, and each length is cycled ten times; the resistance of the sensor when bent is recorded as R, and the response of the pressure sensor is (R-R0) / R0; the electrical signal of the sensor during the cycle is collected by the data acquisition device, and the relationship diagram between resistance and time is obtained; (2) Fit sensor No. 2 to a part of the body and connect it to a data collector with a wire to test the motion response and physiological response; fit the sensor tightly to the finger joints, wrist joints and throat respectively, and then collect the data of the electrical signal through the data collector during the process of bending the fingers, bending the wrists, swallowing and shaking the head; the resistance of the sensor when no action is performed is recorded as R0, and the resistance when performing the above actions is recorded as R, so its response size is (R-R0) / R0; fit sensor No. 2 tightly to the throat and wrist respectively, and test the physiological response produced by normal breathing and deep breathing, reading the word "sensor" and pulse beating; The electrical data were collected by a data logger or an electrochemical workstation.

3. Sn according to claim 1 0.2 Mo 0.8 The application of S2 nanosphere is characterized by: The Sn 0.2 Mo 0.8 The S2 nanospheres are sprayed on the interdigital electrodes and dried to form a film, and then prepared into a chemical resistance sensor that can simultaneously monitor pressure and temperature. 0.2 Mo 0.8 S2 nanocircle nanomaterials not only have high sensitivity and stability, but can also be used in flexible sensing to monitor important human vital signs such as pulse and breathing.

4. A pressure sensing material based on a two-dimensional transition metal chalcogenide nanostructure, characterized in that: Sn according to claim 1 0.2 Mo 0.8 The pressure sensing material of S2 nanosphere is used to prepare pressure sensor devices.

5. A temperature sensing material based on a two-dimensional transition metal chalcogenide nanostructure, characterized in that: Sn according to claim 1 0.2 Mo 0.8 The temperature sensing material of S2 nanosphere is used to prepare temperature sensing devices.